Analysis of summer 2006 ozone pollution in Zagreb - Pehnec, Gordana (Array, 2009)
Summary: In the summer of 2006, ozone concentrations were measured at three sites in the Zagreb area. Stations Velika Gorica (VG), Dugave (DUG), and Institute for Medical Research and Occupational Health (IMI) were located at the same elevation along a 15-km stretch from the Zagreb Airport in the south (VG) to about 2.5 km north from the city centre (IMI). At all three sites, ozone volume fractions showed pronounced diurnal variations, peaking between 15 h and 18 h (VG) and between 13 h and 16 h (DUG, IMI) local time (CEST). Average ozone volume fractions measured in the northern and southern residential part of the town (IMI and DUG) were similar and also showed similar daily pattern. In VG daily variations were more pronounced. The analysis of summer 2006 ozone data clearly shows the highest ozone concentrations at the southernmost point (VG). Because the comparison of diurnal variations at all three stations